A production and operations management study on Leotax Corporation - De Celis, Excel Ann C. (College of Engineering, 2001)
Leotax Corporation is an assembly company that manufactures telescopes for terrestrial and astronomical use. The firm is Japanese owned and is currently supplying to only one customer, Bushnell Corporation. To compete globally, the company is looking into ways by which it can improve its productivity and reformulate the company's strategy to address issues in the international market. The study aims to analyze the production systems that create the firm's primary product line. Tools in Production and Operations Management will be used to determine whether the current production and operations management system of the company is geared towards the company's vision and goals. The study will specifically focus on plant layout, capacity level, workforce level, inventory level and strategic and tactical process decisions. The research paper was done through plant visits between the months of December and February. Company personnel were interviewed to gain an in-depth perspective with the company culture. Organizational structure, layout, capacity, inventory system, raw materials sourcing, and assembly lines were documented. The company currently produces only two models out of the five available models because recession in the United States and cheaper imports from China is limiting the demand. The study showed that the lack of inventory control is creating problems in traceability of raw materials, thus increasing the capital tied up in unnecessary inventory. Informal production planning and an unbalanced assembly line lead to inefficiencies in the production flow. A mixed strategy in aggregate planning is recommended, since it is not an option for the company to fire workers. To improve inventory control, a periodic review system is needed which should be done every month. A transition period is needed to gradually implement the periodic reviews. In support of this, material requirement planning should also be put into operation, with a lot-for-lot order size and a provision for the safety stock. Simple line balancing is sufficient for the needs of the company. Areas of further study include looking into the feasibility and benefits of an aggressive alternatives such as improved marketing, creative pricing and development of new models.